World War One life in the trenches - Hamilton, Robert (History in pictures, 2012)
Superbly illustrated with photographs from the Daily Mail archieves, World War One: life in the trenches tells the extraordinary story of a time and a place where conditions were brutal and soldiers lived in the knowledge that any day could be their last.